PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PADA TAHUN 2019-2023 - Maisaroh, Siti; Pramitasari, Triska Dewi; Nanggala, Ardhya Yudistira Adi (Fakultas Ekonomi dan Bisnis, 2025)
Food and beverage companies listed on the Indonesia Stock Exchange are one of the industrial sectors with rapid growth and significant contributions to the national economy. This study examines the effect of capital structure, company growth, and liquidity on company value directly or indirectly through profitability as an intervening variable. The object of this research is food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The research method used is a quantitative method with a descriptive approach. The sampling technique was purposive sampling, and seven companies were obtained as samples—data obtained from annual financial reports published through the official IDX website. The data analysis technique used is Structural Equation Modeling (SEM) with the help of the Smart PLS application. The results of the direct effect hypothesis test show that capital structure and company growth have a significant effect on profitability but not on company value, liquidity has a significant effect on profitability and company value, profitability has a significant effect on company value. The indirect effect hypothesis test results show that capital structure, company growth, and liquidity on company value through profitability have an insignificant effect.